Implementation of Village Asset Planning and Maintenance Based on the Regulation of the Minister of Home Affairs of the Republic of Indonesia No. 1 of 2016: A Case Study of Kota Bangun Village, Ranomeeto District, South Konawe Regency - Arti Afriliani; Muh. Nur; Yusuf Jaya Saputra; Reyhan Dzikriansyah Sunarno (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2026)
Law Number 6 of 2014 and Minister of Home Affairs Regulation Number 1 of 2016 mandate transparent and participatory village asset management. However, managerial constraints and weak administration often hamper this regulation at the local level. This study aims to analyze the implementation of village asset planning and maintenance in Kota Bangun Village, Ranomeeto District, South Konawe Regency, and its relationship to the principles of Good Government Governance (GGG). Using qualitative descriptive methods with interactive data analysis and triangulation techniques, this research found that asset planning in Kota Bangun Village has been carried out in accordance with regulations through the Village Development Planning Forum (Musrenbangdes) mechanism involving the Village Consultative Body (BPD) and community elements in a bottom-up manner. Conversely, the asset maintenance function has not met the standards of Minister of Home Affairs Regulation Number 1 of 2016 because the village government has not conducted an inventory due to limited human resource capacity and internal administration. The absence of an inventory master book triggers uncertainty about asset volume, obscures ownership status, and hampers maintenance budgeting. Nevertheless, the implementation of the GGG principle shows a positive trend, where budget transparency is able to reduce suspicion and boost public trust. It was concluded that asset planning had met regulatory standards, but the maintenance sector required fundamental improvements related to increasing the administrative capacity of village apparatus human resources.